Pelatihan Manajemen Operasional Pada Budidaya Melon Hidroponik di Kabupaten Bojonegoro - Wati, Hernum Daya (JURNAL PENGABDIAN MANAJEMEN, 2025)
Cultivating plants using hydroponic methods promises better yields compared to conventional methods. However, the use of this technique is still relatively low among the community, especially in Bojonegoro Regency, East Java Province. Therefore, this community service activity is conducted to enhance public knowledge about hydroponic plant cultivation methods and operational management in the hydroponic melon production process in Bojonegoro Regency. The training was held on February 22, 2025, at Greenhouse Sagara Farm, Kenep Village, Balen District, Bojonegoro Regency, and was attended by 11 students from MI Najil Ummah Kenep and 12 students from IKIP PGRI Bojonegoro. The participants were selected based on their communication skills and potential to implement the training for themselves and the surrounding community. . The training uses lectures, discussions, and independent practice methods. Participants’ responses to the training were measured using a questionnaire given at the end of the training session. The results of the analysis of the questionnaire showed that the perception of participants regarding the training activities that had been carried out was included in the very positive category. The majority of participants felt helped by the training activities. The next activity is recommended to integrate more innovative hydroponic techniques. It is hoped that this increase in knowledge and skills will encourage more people to apply the hydroponic method, so that it can increase the income of the community in Bojonegoro Regency. Keywords: Training; Melon hydroponics; Operational Management; Production Process